2016
DOI: 10.1021/acsami.5b09691
|View full text |Cite
|
Sign up to set email alerts
|

Durable Microstructured Surfaces: Combining Electrical Conductivity with Superoleophobicity

Abstract: In this study, electrically conductive and superoleophobic polydimethylsiloxane (PDMS) has been fabricated through embedding Ag flakes (SFs) and Ag nanowires (SNWs) into microstructures of the trichloroperfluorooctylsilane (FDTS)-blended PDMS elastomer. Microstructured PDMS surfaces became conductive at the percolation surface coverage of 3.0 × 10(-2) mg/mm(2) for SFs; the highest conductivity was 1.12 × 10(5) S/m at the SFs surface coverage of 6.0 × 10(-2) mg/mm(2). A significant improvement of the conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…The EGaIn was selected as the conducting material due to its high electrical conductivity, low viscosity, and nontoxicity. [ 34,35 ] The choice of iron particles was projected to improve the conductivity of the elastomer, which has been verified in our previous works. [ 36,37 ] During mixing, EGaIn is broken into microdroplets and embedded between adjacent iron particle chains.…”
Section: Resultsmentioning
confidence: 70%
“…The EGaIn was selected as the conducting material due to its high electrical conductivity, low viscosity, and nontoxicity. [ 34,35 ] The choice of iron particles was projected to improve the conductivity of the elastomer, which has been verified in our previous works. [ 36,37 ] During mixing, EGaIn is broken into microdroplets and embedded between adjacent iron particle chains.…”
Section: Resultsmentioning
confidence: 70%
“…46 Guided by this simple concept, our group started our biomimetic research via the fabrication of surface micropillar structures of polymer (Figure 6a) 47 and investigated their contact behaviors with liquids and solids with the aim of establishing a relationship between surface structures and interfacial properties (Figure 6b−f). [48][49][50][51]54,58 In the following section, we describe two key aspects of our recent research activities on bioinspired interfacial Bioinspired Superhydrophobic Surface with Additives for Multifunctionality. Superhydrophobic surfaces refer to surfaces where the static contact angle for water is >150°.…”
Section: ■ Bioinspired Interfacial Engineeringmentioning
confidence: 99%
“…The relations of stretchability and reversibility were characterized, showing that the Ag flake/Ag nanowireembedded microsurface has better mechanical and electrical performances. 48 Bioinspired Friction, Adhesion, and Dry Adhesives. Friction is the surface resistance of an object to its lateral movement over another surface, and adhesion is the state at which two dissimilar surfaces stick to one another.…”
Section: ■ Bioinspired Interfacial Engineeringmentioning
confidence: 99%
“…Recent studies have shown that polydimethylsiloxane (PDMS) is a soft stamp template with unique advantages in the implementation of nanostructure self-assembly. [28][29][30][31][32] PDMS is transparent with low background Raman scattering. It has high light transmittance, good formability, etc.…”
Section: Introductionmentioning
confidence: 99%